Body representation disorders predict left right orientation impairments after stroke: A voxel-based lesion symptom mapping study. (July 2018) - van Stralen, Haike E.; Dijkerman, H. Chris; Biesbroek, J. Matthijs; Kuijf, Hugo J.; van Gemert, H. Maarten A.; Sluiter, David; Kappelle, L. Jaap; van Zandvoort, Martine J.E.
Abstract: Introduction: Deficits in the ability to distinguish between the left and right side of the body can severely impair daily life functioning. The current study examined the relation between left right orientation (LRO) impairments and somatosensory related deficits, ranging from primary somatosensory impairments to body representation impairments, in patients who suffered a recent stroke. We also examined which areas in the brain are associated with LRO impairments using a Voxel-based Lesion Symptom Mapping (VLSM) analysis. Method: We tested 47 first-ever stroke patients and 48 age-matched healthy controls. LRO was assessed with the Bergen Right Left Discrimination Test (BRLD). Impairments on primary somatosensory function (touch perception, proprioception), higher order somatosensory function (finger gnosis, subjective sense of body ownership) and other cognitive functions (language, attention & working memory, visuospatial neglect) were entered as predictors in a logistic regression analyses. Outcome measures consisted of the BRLD-total performance which was further subdivided in performance for 1) first person perspective stimuli, 2) third person perspective stimuli, 3) alternating between first- and third person perspective. Results: Impairments on BRLD-total performance was predicted by impairments in finger gnosis and visuospatial neglect. For items placed in third person perspective, performance was predicted by body representation impairments; finger agnosia and the subjective sense of body ownership. VLSM analysis showed a significant association between LRO impairments and damage to the right insula. Discussion: The current study suggests that the somatosensory system is important for LRO. Furthermore, the results indicate that an affected body representation may hinder adopting a third person perspective that may subsequently also lead to LRO impairments. The right insular cortex appeared crucially involved in these processes.